Mipog : a parallel t-way minimization strategy for combinatorial testing - Al-Khiro, Mohammed Issam Younis (2010)
Combinatorial testing has been an active research area in recent years. One challenge in this area is dealing with the combinatorial explosion problem, which typically requires a very expensive computational process to find a good test set that covers all the combinations for a given interaction strength (t). Parallelization can be an effective approach to manage this computational cost, that is, by taking the recent advancement of multicore and GRID architectures. Motivated by such alluring prospects and challenges, this thesis discusses the design, implementation, and evaluation of an efficient parallelizable t-way strategy, called MIPOG (Modified IPOG) strategy based on its predecessor IPOG (In Parameter Order General) strategy, for systematic t-way test data minimization. Unlike earlier work, the MIPOG optimizes and removes the dependencies between parameter and values. In this manner, MIPOG permits the possibility for exploiting parallel computing.